Increased DSG2 plasmatic levels identified by transcriptomic-based secretome analysis is a potential prognostic biomarker in laryngeal carcinoma - Cury, Sarah Santiloni [UNESP]; Lapa, Rainer Marco Lopez [UNESP]; de Mello, Julia Bette Homem; Marchi, Fábio Albuquerque; Domingues, Maria Aparecida Custódio [UNESP]; Pinto, Clóvis Antonio Lopes; Carvalho, Robson Francisco [UNESP]; de Carvalho, Genival Barbosa; Kowalski, Luiz Paulo; Rogatto, Silvia Regina (Elsevier, 2020)
Objectives: The tumor secretome deconvolution is a promising strategy to identify diagnostic and prognostic biomarkers. Here, transcriptomic-based secretome analysis was performed aiming to discover laryngeal squamous cell carcinomas (LSCC) biomarkers from potentially secreted proteins (PSPs). Material and Methods: The tumor expression profile (35 LSCC biopsies compared with surrounding normal tissues - SN) revealed 589 overexpressed genes. This gene list was used for secretome analysis based on laryngeal tumors and related secretome databases. Results: Forty-nine (Laryngeal tumor secretome database) and 50 (Human Protein Atlas and Cancer Secretome Database) PSPs presented an association with worse overall survival. Specifically, DSG2 overexpression was strongly correlated with poor survival and distant metastasis. DSG2 increased expression was confirmed in the LSCC dataset (LSCC = 111; SN = 12) from TCGA. A significant association between shorter survival and DSG2 overexpression was also detected. In an independent cohort of cases, we analyzed and confirmed high protein levels of DSG2 in plasma from LSCC patients. Conclusion: A set of PSPs including the circulating DSG2, were associated with shorter overall survival in LSCC. DSG2 overexpression was also correlated with distant metastasis. The high plasmatic protein levels of DSG2 suggest its potential to be tested in liquid biopsies and applied as prognostic biomarker of LSCC.
Keywords: Biomarker; Laryngeal squamous cell carcinoma; Liquid biopsy; Secretome; Transcriptome